Atypical Integration of Sensory-to-Transmodal Functional Systems Mediates Symptom Severity in Autism - Park, Shinwon; Haak, Koen V.; Cho, Han Byul; Valk, Sofie L.; Bethlehem, Richard A. I.; Milham, Michael P.; Bernhardt, Boris C.; Di Martino, Adriana; Hong, Seok-Jun (Frontiers in Psychiatry, 2021)
A notable characteristic of autism spectrum disorder (ASD) is co-occurring deficits in low-level sensory processing and high-order social interaction. While there is evidence indicating detrimental cascading effects of sensory anomalies on the high-order cognitive functions in ASD, the exact pathological mechanism underlying their atypical functional interaction across the cortical hierarchy has not been systematically investigated. To address this gap, here we assessed the functional organisation of sensory and motor areas in ASD, and their relationship with subcortical and high-order transmodal systems. We applied advanced connectopic mapping to probe functional organization of primary sensory/motor areas, together with targeted seed-based intrinsic functional connectivity (iFC) analyses. Our results show that in ASD, the connectopic mapping revealed topological anomalies (i.e., excessively more segregated iFC) in the motor and visual areas, the former of which patterns showed association with the symptom severity of restricted and repetitive behaviors. Moreover, the seed-based analysis found diverging patterns of ASD-related connectopathies: decreased iFCs within the sensory/motor areas but increased iFCs between sensory and subcortical structures. While decreased iFCs were also found within the higher-order functional systems, the overall proportion of this anomaly tends to increase along the level of cortical hierarchy, suggesting more dysconnectivity in the higher-order functional networks. Finally, we demonstrated that the association between low-level sensory/motor iFCs and clinical symptoms in ASD was mediated by the high-order transmodal systems, suggesting pathogenic functional interactions along the cortical hierarchy. Findings were largely replicated in the independent dataset. Collectively, our findings suggest clinical utility of connectopic mapping and targeted iFC analyses, which may be developed into an effective biomarker that takes into consideration the integrative properties of multiple hierarchical functional brain systems in the context of heterogeneous symptom manifestation in ASD.